Project-Based Learning for Design of Concrete Structures with Application of Structural Design Skills and Industry Readiness - Thoriya, Amit; Rangwala, Husain; Modi, Ravi; Vora, Tarak (Journal of Engineering Education Transformations, 2026)
This study evaluates the efficacy of Project-Based Learning (PBL) in the Design of Concrete Structures (DCS) course for Civil Engineering students, targeting Course Outcomes (COs) related to IS code application (CO1), structural design (CO2-CO3), and earthquake analysis (CO4). PBL was implemented through modular projects on water tank modelling, retaining wall design, flat slab analysis, and G+3 building design, assessed via Continuous Semester Evaluation, Term Work, Viva, Internal Assessment, and End Semester Examination. The PBL framework integrated real-world design problems, IS codes, and software tools such as ETABS and SAP2000 to promote hands-on and collaborative learning. Students engaged in modelling, design verification, and presentation tasks that linked theory to practice. The approach led to noticeable improvement in design accuracy, understanding of IS code provisions, software proficiency, and teamwork. Learner feedback indicated stronger engagement and confidence in structural design tasks. Overall, the results confirm that project-based learning substantially enhanced both technical and non-technical competencies, offering a scalable model for developing industry-ready graduates in structural engineering education.